2021
DOI: 10.1002/jsf2.24
|View full text |Cite
|
Sign up to set email alerts
|

Presence, formation, and elimination of foodborne pathogen persisters

Abstract: Foodborne pathogen persisters are a subgroup of genetic susceptibility and growth arrest.They survive antimicrobial stress by stopping their growth, and can regenerate into normal sensitive bacteria after the stress is removed. Foodborne pathogens can survive by resisting unfavorable factors through the mechanism of persisters and exist for a long time in many food-related environments. These surviving bacteria are harmful to food safety and human health. There are many ways to remove persisters, but few of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…This is further supported by the resazurin metabolic assay which revealed that V. parahaemolyticus biofilm cells were able to survive exposure to media with low pH (3) and in SGF which had a pH of 1.5 for 2 h, but V. vulnificus did not recover as well or survive. However, this survival could be due to the presence of persister cells, as these cells were able to survive the stressors, and once the stressor was removed, were able to become metabolically active again and the biofilms recover in growth and development ( Xiong et al, 2022 ). V. parahaemolyticus , while not being isolated from blood, still had high amounts of biofilm biomass, biofilm cell concentrations, cell colonization and dispersal in HPLM at 25°C and 37°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further supported by the resazurin metabolic assay which revealed that V. parahaemolyticus biofilm cells were able to survive exposure to media with low pH (3) and in SGF which had a pH of 1.5 for 2 h, but V. vulnificus did not recover as well or survive. However, this survival could be due to the presence of persister cells, as these cells were able to survive the stressors, and once the stressor was removed, were able to become metabolically active again and the biofilms recover in growth and development ( Xiong et al, 2022 ). V. parahaemolyticus , while not being isolated from blood, still had high amounts of biofilm biomass, biofilm cell concentrations, cell colonization and dispersal in HPLM at 25°C and 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…This likely occurs as cells embedded in biofilms survive the sudden changes in temperature and pH in a new environment like the human gastrointestinal tract. When environmental conditions are more favorable, the cells disperse from the consumed abiotic or biotic surface, which can lead to colonization of the gastrointestinal surfaces ( Motta et al, 2021 ; Xiong et al, 2022 ). One of these abiotic surfaces can be MPs, and since Vibrio biofilms have been abundantly found on MPs, one implication is that MPs could act as transport vectors of pathogenic Vibrio species to marine animals that coincidently or selectively ingest biofilm-associated MP particles instead of food particles in the marine environment.…”
Section: Introductionmentioning
confidence: 99%